Artificial intelligence/machine learning for wealth management - Teo, Wee Ren (Nanyang Technological University, 2022)
Over the years, machine learning and Artificial intelligence have been making exponential advancements due to improvements in technology and computational power. They are rapidly transforming industries and societies in the world. Machine learning and Artificial intelligence are now available to everyone that is connected to the internet. It is no longer a concept that huge organizations can only implement. The paper proposes to capitalize on the available machine learning libraries and build a web application around them to provide users with information and knowledge to invest in the stock market. The web application aims to give recommendations and guidance on the stock they are interested in. The application's front end is created using a popular JavaScript framework called React.